Döden på museet : Mänskliga kvarlevor och samtal om döden i museipedagogiska verksamheter - Görnerup,Amanda (2021)
The purpose of this master’s thesis is to examine on how three museums in Skåne uses human remains from their collections in pedagogical work with children. With the help of interviews with staff members and observations in the museum exhibitions, text and image analysis, the human remains are closely observed. Furthermore, the analysis part of the thesis uses the theoretical viewpoint of materiality and materialisation. The interviews and observations emphasise on different recurring themes in how the museums use and approach their human remains. The thesis also highlights the difference in the museum’s attitudes concerning the ethical and moral implications that comes with exhibiting human remains. Analysing the different materials, the complicated materialisation of human remains becomes clear.
Keywords: Museum; mänskliga kvarlevor; döden; pedagogisk verksamhet; materialitet; materialisering; utställningar Museum; human remains; death; pedagogical settings; materiality; materialisation; exhibitions